Capacity of unreinforced rammed earth walls subject to lateral wind force: elastic analysis versus ultimate strength analysis - Ciancio, D.; Augarde, C. (Materials and structures, 2013)
Cement-stabilized rammed earth walls are an increasingly common form of construction in certain parts of the world, bringing considerable potential to reduce the carbon footprints of buildings. However, there is relatively little advice to designers wishing to use these construction materials at present, as compared to established materials such as concrete. This paper discusses the use of two proposed analysis procedures to calculate the capacity of unreinforced cement-stabilized rammed earth walls to lateral wind force. The first is an elastic analysis while the second is an ultimate strength analysis where a cracked wall is studied as a rigid-body mechanism. The accuracy of each method is assessed against the results of an experimental programme conducted on different rammed earth walls showing the shortcomings of the ultimate strength analysis. A new method is proposed in which the fracture energy required to open the crack that leads to the failure mechanism is included, leading to much improved predictions. The parameters used in the revised ultimate strength analysis are critically discussed and compared to those found in the concrete and masonry literature.